A long night in Paris - Alfon, Dov, 1961- (Pegasus Crime, 2020)
"When an Israeli tech executive disappears from Charles de Gaulle airport with a woman in red at his side, logic dictates youthful indiscretion. Israel is on a state of high alert nonetheless. And for Commissaire Leger of the Paris Police Force, all coincidences are suspect. When a second young Israeli from the flight is kidnapped, this time at gunpoint from his hotel room, his suspicions are confirmed--and a diplomatic crisis looms. As the race to identify the reasons behind the abductions intensifies, a covert Chinese commando team watches from the rooftops--while hour by hour the morgue receives fresh bodies from around Paris. This could be one long night in the City of Lights"--